2017
DOI: 10.4183/aeb.2017.342
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hemiagenesis Associated with Graves' Disease: A Case Report and Review of the Literature

Abstract: Introduction. Thyroid hemiagenesis (TH) is a congenital developmental disorder. Most cases are euthyroid although hyperthyroidism, hypothyroidism, and malignancy may develop. We present a case of hemiagenesis with Graves' disease (GD) and review the literature about the association. Case report. A 45-year-old female patient was admitted to the endocrinology department due to nausea and diarrhea. Her past medical history revealed hyperthyroidism diagnosed a year ago. On thyroid examination, right thyroid lobe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, large Fig. 1 Ultrasound of the thyroid gland with high frequency linear probe demonstrating a Absent left thyroid lobe b The right thyroid lobe normal tissue volume, and c Isthmus in situ both in longitudinal and transverse planes case-control studies observed a significantly higher incidence of concomitant thyroid disorders such as Gravesʼ disease, Hashimotoʼs thyroiditis, subacute thyroiditis, nodular goiter, hyperfunctioning adenoma, primary carcinoma, and metastatic carcinoma, in patients with THA than in those with bilobate thyroid glands, the most frequent disorders being thyroid nodules and autoimmune thyroid diseases [8,11]. We found a solitary thyroid nodule in the present case of THA as a reason to seek medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, large Fig. 1 Ultrasound of the thyroid gland with high frequency linear probe demonstrating a Absent left thyroid lobe b The right thyroid lobe normal tissue volume, and c Isthmus in situ both in longitudinal and transverse planes case-control studies observed a significantly higher incidence of concomitant thyroid disorders such as Gravesʼ disease, Hashimotoʼs thyroiditis, subacute thyroiditis, nodular goiter, hyperfunctioning adenoma, primary carcinoma, and metastatic carcinoma, in patients with THA than in those with bilobate thyroid glands, the most frequent disorders being thyroid nodules and autoimmune thyroid diseases [8,11]. We found a solitary thyroid nodule in the present case of THA as a reason to seek medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hemiagenesis is an extremely rare developmental disorder of the thyroid, 10 but it may become apparent during surveillance for thyroid diseases such as thyroid tumor, carcinoma, or Graves' disease. [9][10][11] Thyroid hemiagenesis is caused by one side of the thyroid not developing embryologically, rather than a failure of glandular tissue descent or migration, as seen in ectopic thyroid. 7,30 Regarding laterality, past reports have shown many cases of thyroid hemiagenesis are on the left side.…”
Section: Discussionmentioning
confidence: 99%
“…Defects on the right side, as in this case, are rare. 10 The incidence of thyroid hemiagenesis is estimated to be approximately 0.02%. 30 It tends to be more common in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another very rare scenario involves the concomitant diagnosis of PHP and giant-goitre-associated thyrotoxicosis; in this situation, hypercalcaemia-related hyperthyroidism may mask the biological recognition of PHP and 99m-Tc sestamibi scintigraphy might be found as false negative at baseline [74]. Also, 99m-Tc scintigraphy has been used for thyroid hemi-agenesis, showing an increased unilateral uptake amid this interesting developmental disease of the gland [75,76].…”
Section: Ectopic Thyroid Tissuementioning
confidence: 99%